2004
DOI: 10.1038/nature02785
|View full text |Cite
|
Sign up to set email alerts
|

Vigorous exchange between the Indian and Atlantic oceans at the end of the past five glacial periods

Abstract: The magnitude of heat and salt transfer between the Indian and Atlantic oceans through 'Agulhas leakage' is considered important for balancing the global thermohaline circulation. Increases or reductions of this leakage lead to strengthening or weakening of the Atlantic meridional overturning and associated variation of North Atlantic Deep Water formation. Here we show that modern Agulhas waters, which migrate into the south Atlantic Ocean in the form of an Agulhas ring, contain a characteristic assemblage of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

21
493
4
7

Year Published

2007
2007
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 377 publications
(525 citation statements)
references
References 27 publications
(53 reference statements)
21
493
4
7
Order By: Relevance
“…[49] Several studies of the Southeast Atlantic have concluded that the supply of Agulhas water to the Atlantic was reduced substantially during glacial times [Flores et al, 1999;Kuhn and Diekmann, 2002;Peeters et al, 2004;Franzese et al, 2006]. Furthermore, as the Agulhas system and the Drake Passage are the two primary avenues for return flow to the North Atlantic [Gordon et al, 1992], the glacial reduction in supply of Agulhas water may have been compensated for by increased supply via the Drake Passage.…”
Section: Pa4216mentioning
confidence: 99%
“…[49] Several studies of the Southeast Atlantic have concluded that the supply of Agulhas water to the Atlantic was reduced substantially during glacial times [Flores et al, 1999;Kuhn and Diekmann, 2002;Peeters et al, 2004;Franzese et al, 2006]. Furthermore, as the Agulhas system and the Drake Passage are the two primary avenues for return flow to the North Atlantic [Gordon et al, 1992], the glacial reduction in supply of Agulhas water may have been compensated for by increased supply via the Drake Passage.…”
Section: Pa4216mentioning
confidence: 99%
“…sensus Peeters et al, 2004) at ODP Site 1088 do not increase in relative abundance and therefore the warming cannot be attributed to increased circulation of warm Agulhas water at the site. This observation is similar to those made in a micropalaeontological study of site TNO57-21 over the last deglaciation (Barker et al, 2009).…”
Section: Accepted M Manuscriptmentioning
confidence: 89%
“…10 seaway during the late Quaternary can be found in Peeters et al, (2004), andin O'Neil et al, (2007) for the middle Pleistocene.…”
Section: Accepted M Manuscriptmentioning
confidence: 97%
See 1 more Smart Citation
“…Over 2-4 decades the warm salty water that enters the South Atlantic is advected northwards (Ruhs et al 2013;Weijer et al 2001), its influence on the buoyancy balance affects deep water formation, the AMOC and thus global climate. Paleoceanographic studies and foram assemblages indicate that fluctuations in the strength of AL are linked to the glacial/interglacial cycles and periods of variable AMOC (Peeters et al 2004;Caley et al 2014). With the potential of increasing leakage to warm the climate (Beal et al 2011), the importance of the Agulhas system and its role in the global climate and circulation makes understanding the drivers of variability very important.…”
Section: Introductionmentioning
confidence: 99%